2000
DOI: 10.1046/j.1365-2958.2000.01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid resistance of Helicobacter pylori depends on the UreI membrane protein and an inner membrane proton barrier

Abstract: ureI encodes an inner membrane protein of Helicobacter pylori. The role of the bacterial inner membrane and UreI in acid protection and regulation of cytoplasmic urease activity in the gastric microorganism was studied. The irreversible inhibition of urease when the organism was exposed to a protonophore (3,3′,4′,5‐tetrachlorsalicylanide; TCS) at acidic pH showed that the inner membrane protected urease from acid. Isogenic ureI knockout mutants of several H. pylori strains were constructed by replacing the ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…However, with regards to characterization of one key residue, His-123, the results of Bury-Mone et al (10) were found to contradict the findings obtained using Xenopus oocytes. With the exception of this report by Bury-Mone and colleagues (10), functional descriptions of HpUreI expressed in oocytes and H. pylori have been indistinguishable (17). Further, the urea channel of Yersinia pseudotuberculosis, Yut, has been shown to function similarly both in oocytes and in H. pylori (4).…”
Section: Discussionmentioning
confidence: 73%
“…However, with regards to characterization of one key residue, His-123, the results of Bury-Mone et al (10) were found to contradict the findings obtained using Xenopus oocytes. With the exception of this report by Bury-Mone and colleagues (10), functional descriptions of HpUreI expressed in oocytes and H. pylori have been indistinguishable (17). Further, the urea channel of Yersinia pseudotuberculosis, Yut, has been shown to function similarly both in oocytes and in H. pylori (4).…”
Section: Discussionmentioning
confidence: 73%
“…Mutants were made according to a published procedure that is only presented in outline here (30). Standard procedures (31) were used for isolation and treatment of plasmid DNA.…”
Section: Methodsmentioning
confidence: 99%
“…The electroporated bacteria were plated onto LB plates (LB agar base; GIBCO BRL) supplemented with 50 mg/mL ampicillin. The DNA was generated by PCR of selected primers as detailed previously (30).…”
Section: Methodsmentioning
confidence: 99%
“…UreI (21.7 kDa) is a proton-gated inner membrane protein involved in urea transport as well as acid resistance (Rektorschek et al 2000;Skouloubris et al 1998). UreI possesses six membrane-spanning segments and conserved histidine residues, including His123, are essential for acid activation of the channel (Bury-Mone et al 2001;Weeks et al 2000;Weeks and Sachs 2001).…”
Section: Accessory Proteins For Urease Maturationmentioning
confidence: 99%